Catalytic transformation of levulinic acid to 2-methyltetrahydrofuran using ruthenium–N-triphos complexes - Phanopoulos,A; White,AJ; Long,NJ; Miller,PW (ACS Catalysis, 2015)
A series of pre- or in situ-formed ruthenium complexes were assessed for the stepwise catalytic hydrogenation of levulinic acid (LA) to 2-methyltetrahydrofuran (2-MTHF) via γ-valerolactone (γVL) and 1,4-pentanediol (1,4-PDO). Two different catalytic systems based on the branched triphosphine ligands Triphos (CH3C(CH2PPh2)3) and N-triphos (N(CH2PPh2)3) were investigated. The most active catalyst was the preformed ruthenium species [RuH2(PPh3){N(CH2PPh2)3-κ3P}] (5), which gave near quantitative conversion of LA to 1,4-PDO when no acidic additives were present, and 87% 2-MTHF when used in conjunction with HN(Tf)2. Various acidic additives were assessed to promote the final transformation of 1,4-PDO to 2-MTHF; however, only HN(Tf)2 was found to be effective, and NH4PF6 and para-toluenesulfonic acid (p-TsOH) were found to be detrimental. Mechanistic investigations were carried out to explain the observed catalytic trends and importantly showed that PPh3 dissociation from 5 resulted in its improved catalytic reactivity. The presence of acidic additives removes catalytically necessary hydride ligands and may also compete with the substrate for binding to the catalytic metal center, explaining why only an acid with a noncoordinating conjugate base was effective. Crystals suitable for X-ray diffraction experiments were grown for two complexes: [Ru(NCMe)3{N(CH2PPh2)3-κ3P}] (14) and [Ru2(μ-Cl)3{N(CH2PPh2)3-κ3P}2][BPh4] (16).